Caring and striving: toward a new consumer identity in the process of consumption reduction - Callmer, Åsa; Boström, Magnus (Frontiers in Sustainability, 2024)
Adoption of sufficiency-oriented lifestyles is an important part of curbing overconsumption, yet many individuals who try to reduce their consumption volumes experience social difficulties. Combining the perspectives of care and sufficiency-oriented lifestyle changes, this article aims to contribute to the understanding of why such social obstacles occur, how they might be counteracted and in what ways social relations instead may facilitate consumption reduction. Building on a processual theory of consumer identity, the perspective of care, and an interview study with 25 Swedish consumption reducers, this article discusses how care and consumption are (re)negotiated in the different stages of reduction. The analysis shows that consumption reduction in many ways is an ongoing process of both caring and striving. By highlighting the different aspects of care involved in consumption reduction and how it is renegotiated in a gradual construction of a caring consumer identity, this article shows the importance of maintaining a sensitivity to the multi-faceted nature of care, acknowledging it both as a source of difficulties and as a key driver for sufficiency-oriented lifestyle changes. one's ambitions due to social inconveniences, and (in the case of parents) worry about one's children